Intermittent preventive treatment of pregnant women in Kintampo area of Ghana with sulphadoxine-pyrimethamine (SP): trends spanning 2011 and 2015. Issue 6 (22nd June 2019) - Oppong, Felix Boakye; Gyaase, Stephaney; Zandoh, Charles; Nettey, Obed Ernest A; Amenga-Etego, Seeba; Anane, Edward Apraku; Adda, Robert; Dosoo, David Kwame; Owusu-Agyei, Seth; Asante, Kwaku Poku
Abstract : Objective: In Ghana, intermittent preventive treatment during pregnancy with sulphadoxine-pyrimethamine (IPTp-SP) is recommended for the prevention of malaria-related adverse outcomes. This study demonstrates the coverage of IPTp-SP use among pregnant women over a period (2011–2015) and the impact of various sociodemographic groups on the uptake of IPTp-SP. Design: Retrospective analysis using data from all pregnant women in the Kintampo Health and Demographic Surveillance System area on the uptake of IPTp-SP. Setting: Kintampo North Municipality and Kintampo South District of Ghana. Participants: All pregnant women in the Kintampo Health and Demographic Surveillance System area. Primary and secondary outcome measures: The number of doses of IPTp-SP taken by pregnant women were examined. Logistic regression was used to assess the determinant of uptake of IPTp-SP while adjusting for within-subject correlation from women with multiple pregnancies. Results: Data from 2011 to 2015 with a total of 17 484 pregnant women were used. The coverage of the recommended three or more doses of IPTp-SP among all pregnant women was 40.6%, 44.0%, 45.9%, 20.9% and 32.4% in 2011, 2012, 2013, 2014 and 2015, respectively. In the adjusted analysis, age, household size, education, religion, number of antenatal care visits, ethnicity, marital status, wealth index and place of residence were significantly associated with the uptake of three or more doses of IPTp-SP. Having middle school education or higher, aged 20 years and above, visiting antenatal care five times or more (OR 2.83, 95% CI 2.64 to 3.03), being married (OR 1.10, 95% CI 1.02 to 1.19) and those in higher wealth quintiles were significantly more likely to take three or more doses of IPTp-SP. Conclusion: The uptake of the recommended three or more doses of IPTp-SP is low in the study area. We recommend a community-based approach to identify women during early pregnancy and to administer IPTp-SP.